THE EFFECT OF DIETARY HIGH FAT AND LOW PROTEIN ON BODY WEIGHT AND HISTOLOGICAL NATURE OF COLON IN BALB/C MICE - Hadeel T. Al-Hadithi; Dhamia K. Suker; Zaineb R. Abdul-Hussein (Basrah Journal of Veterinary Research)
The effect of three dietary regimes: - high fat ((1-If), low protein (Lp), and High. fat low protein (HfLp) was studied on 3 groups of 21 days old Balb/c mice .A fourth group received balanced diet as ' control (C). histological pictures of large intestine (colon) was examined after 3,6,l2 weeks after weaning time (day 0) ofexperiment .body weight was determined on weekly bases for the four groups. Significant differences were detected amongmeans of body weights ofexperimental animals in comparison with control group as following: - Hf>C>HfLp>LP. — ' - Profound histological changes of colon were observed specially in the Hﬂp group in process of time. Significant differences in numbers of goblet cells and thickness ofthe adventitial layer of colon was detected, the numbers of goblet cells were reduced in LP group, while their numbers increased in Hf group.